Blimp-1-Mediated Pathway Promotes Type I IFN Production in Plasmacytoid Dendritic Cells by Targeting to Interleukin-1 Receptor-Associated Kinase M - Ko, Yi-An; Chan, Yueh-Hsuan; Liu, Chin-Hsiu; Liang, Jian-Jong; Chuang, Tsung-Hsien; Hsueh, Yi-Ping; Lin, Yi-Ling; Lin, Kuo-I (Frontiers in Immunology, 2018)
Plasmacytoid dendritic cells (pDCs) are a specialized subset of DCs capable of rapidly producing copious amounts of type I IFN (IFN-I) in response to viral infections. The mechanism regulating rapid production of IFN-I after pDCs are exposed to viral nucleic acids remains elusive. Here, we show that the transcription factor Blimp-1 is promptly induced in pDCs after exposure to TLR7 and TLR9 ligands via a unique Ras-related C3 botulinum toxin substrate (Rac)-mediated pathway. Deletion of the Prdm1 gene encoding Blimp-1 impaired production of IFN-I, but not other cytokines, upon viral infection or treatment with CpG DNA in pDCs. Accordingly, mice lacking Blimp-1 in DCs failed to produce IFN-I after CpG stimulation and did not mount proper antiviral responses following flavivirus infection. The development of pDCs in bone marrow as well as the induction of several activation markers, such as CD86, CD69 and MHCII, by CpG stimulation was generally not affected by the absence of Blimp-1. Mechanistically, we found that Blimp-1 controls the activation of IKKα and IRF7 by directly suppressing Interleukin-1 receptor-associated kinase 3 (Irak3), a negative regulator of TLR signaling, in pDCs. Together, we identify a Blimp-1-dependent pathway that rapidly facilitates IFN-I production by relieving Interleukin-1 receptor-associated kinase M (IRAK-M), encoded by Irak3, in pDCs.